PENGARUH BRAND IMAGE DAN BIAYA PENDIDIKAN TERHADAP KEPUTUSAN MAHASISWA DALAM MEMILIH PROGRAM STUDI MANAJEMEN DI STIE RAHMANIYAH SEKAYU (STUDI KASUS MAHASISWA PROGRAM STUDI MANAJEMEN ANGKATAN 2013/2014) - Ade Nia Suryani (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2018)
This study aims to determine: (1) the influence of brand image and cost of education partially to the student's decision in choosing Management Study Program at STIE Rahmaniyah Sekayu, (2) influence of brand image and educational cost simultaneously to student decision in choosing Management Studies Program STIE Rahmaniyah Sekayu. This research is a causality research. The population of this study is a student of Management Studies Program of 2013/2014 as much as 360 people. The number of samples of 79 people was determined using Slovin formula with a margin of error of 10%. The sample was chosen by using purposive sampling technique. Data were collected by using questionnaire method and analyzed by using multiple linear regression analysis. The result of the research shows that (1) brand image have an effect on student's decision in choosing Management Study Program at STIE Rahmaniyah Sekayu, (2) education cost influence to student decision in choosing Management Study Program at STIE Rahmaniyah Sekayu, (3) brand image and cost of education influence student's decision in choosing Management Study Program at STIE Rahmaniyah Sekayu.